Heightened Brain Response to Pain Anticipation in High-Functioning Adults with Autism Spectrum Disorder - Gu, Xiaosi (Eur J Neurosci, 2017)
Autism spectrum disorder (ASD) is marked by both socio-communicative difficulties and abnormalities in sensory processing. Much of the work on sensory deficits in ASD has focused on tactile sensations and the perceptual aspects of somatosensation, such as encoding of stimulus intensity and location. Although aberrant pain processing has often been noted in clinical observations of patients with ASD, it remains largely uninvestigated. Importantly, the neural mechanism underlying higher-order cognitive aspects of pain processing such as pain anticipation also remains unknown. Here we examined both pain perception and anticipation in high functioning adults with ASD and matched healthy controls (HC) using an anticipatory pain paradigm in combination with functional magnetic resonance imaging (fMRI) and concurrent skin conductance response (SCR) recording. Participants were asked to choose a level of electrical stimulation that would feel moderately painful to them. Compared to HC group, ASD group chose a lower level of stimulation prior to fMRI. However, ASD participants showed greater activation in both rostral and dorsal anterior cingulate cortex during the anticipation of stimulation, but not during stimulation delivery. There was no significant group difference in insular activation during either pain anticipation or perception. However, activity in the left anterior insula correlated with SCR during pain anticipation. Taken together, these results suggest that ASD is marked with aberrantly higher level of sensitivity to upcoming aversive stimuli, which may reflect abnormal attentional orientation to nociceptive signals and a failure in interoceptive inference.